'Me, a teacher?!' – Professional role identification and role activation of psychology PhD students. (17th June 2019) - Hillbrink, Alessa; Jucks, Regina
Abstract : Purpose: Developing professional identities as both researchers and teachers is core to doctoral students' growth. Given the primacy of research for the university career, this study aimed at answering the following questions: how much do doctoral students identify with the teacher compared to the researcher role? Can the teacher role identity be purposely activated? Design/methodology/approach: In an experimental study with 167 psychology PhD students, trait role identification was measured using a questionnaire. Afterward, participants were randomly assigned to one of three conditions differing in the picture material (research vs teaching pictures vs a mixture of both) provided for creating a collage reflecting their roles. Subsequently, answers to open questions were coded and quantified as indicators of state role identity. Findings: As a trait, doctoral students identified more strongly with their researcher role than with their teacher role. Teacher role identity as a state was successfully activated when doctoral students engaged with teaching pictures compared to the other conditions. Practical implications: As the researcher role seems to be the default setting for PhD students, activation of the teacher role has the potential to benefit work satisfaction of PhD students and the quality of their teaching. Originality/value: Taking both long- and short-term identification processes in PhD students into account is a promising new approach. Besides, quantitative data are added to the field of qualitative insights on PhD students' professional roles.